G220(P) The role of ultrasound and paediatric appendicitis score in the diagnosis of appendicitis in children. (25th October 2020) - Gudka, K; Khurram, R; Halim, H; Hagh, S; Suliman, I
Abstract : Aims: Appendicitis is the most common abdominal surgical emergency in children. However, the diagnosis can often prove to be challenging. The aim of this study was to evaluate the role of ultrasound and clinical scoring tools such as paediatric appendicitis score (PAS) in facilitating the diagnosis of appendicitis in children who underwent an emergency appendicectomy. Methods: We retrospectively analysed the clinical records and preoperative imaging of a total of 39 patients under the age of 18 who underwent an emergency laparoscopic or open appendicectomy over a 6 month period between November 2018 and May 2019. Clinical history, examination findings and laboratory data were used to calculate PAS. The diagnostic performance of PAS and ultrasound were evaluated using histopathology as the gold standard to confirm the diagnosis of appendicitis. Results: Overall, there was a 13% negative appendicectomy rate. 20 appendicectomies (51%) occurred in the high risk PAS group (PAS ≥7), and this correlated with 100% positive histology for appendicitis. This compares with the intermediate risk PAS group (PAS 4–6) which had positive histology in 72% (13 children). 8 children (40%) with a high PAS underwent an ultrasound preoperatively, compared to 18 children (100%) with an intermediate PAS. When compared to the data from April – September 2018, there has been a 12% reduction in use of ultrasound in high risk PAS (52% to 40%). The was a delay of 11 hours in time taken to theatre between those children who had an ultrasound scan pre-operatively compared to those who did not. Conclusions: Despite there being some improvement, ultrasound is still being used extensively to investigate appendicitis in children. Overall PAS was a better tool than ultrasound in diagnosing appendicitis. This study has emphasised the importance of clinically risk stratifying patients into high, intermediate and low risk PAS. Ultrasound requests should be reduced in high risk PAS children due to delays in definitive treatment and a 0% negative appendicectomy rate. This in turn, should positively impact outcomes such as length of hospital admission, perioperative and postoperative complications.